2015
DOI: 10.5812/jjm.19579
|View full text |Cite
|
Sign up to set email alerts
|

Post-vaccination Immunity Against Hepatitis B Virus and Predictors for Non-responders Among Medical Staff

Abstract: Background:Hepatitis B virus (HBV) is a major cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). HB vaccination is an essential step in the prevention of the disease and its consequent complications.Objectives:Immune status of medical personnel in teaching hospitals of Khuzestan is not well known. Since these personnel are usually at risk of needle stick and other high-risk events, some challenges exist in infection control committee with regard to managing these events. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
13
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
10
13
0
4
Order By: Relevance
“…A previous meta-analysis in 2002 observed many factors influencing response to hepatitis B vaccine, especially a decrease response to recombinant HBV vaccine at higher ages11, which suggested that earlier vaccination should be prioritized for prevention at the population level. However, in the last decade, numerous emerging reports, which focused on the seroprotection rate of hepatitis B vaccine in adults12131415161718192021222324252627282930313233343536373839404142434445464748, are still inconclusive to immunize what adults are the most appropriate in order to increase the seroprotection rate. Factors influencing immunologic response to hepatitis B vaccine in adults have been inconsistently examined in existing studies.…”
mentioning
confidence: 99%
“…A previous meta-analysis in 2002 observed many factors influencing response to hepatitis B vaccine, especially a decrease response to recombinant HBV vaccine at higher ages11, which suggested that earlier vaccination should be prioritized for prevention at the population level. However, in the last decade, numerous emerging reports, which focused on the seroprotection rate of hepatitis B vaccine in adults12131415161718192021222324252627282930313233343536373839404142434445464748, are still inconclusive to immunize what adults are the most appropriate in order to increase the seroprotection rate. Factors influencing immunologic response to hepatitis B vaccine in adults have been inconsistently examined in existing studies.…”
mentioning
confidence: 99%
“…Suponemos que existen otros factores que impiden una adecuada respuesta inmune. En relación al peso un estudio reporta que en personal de salud un índice de masa corporal (IMC) <42 k/m 2 se asocia a 3% de falta de respuesta, mientras que con IMC ≥42 k/m 2 esa frecuencia aumenta a 14,9% (19) . En nuestro reporte, la obesidad resultó un factor de riesgo significativo (p 0,02) de mala respuesta a la vacuna.…”
Section: Discussionunclassified
“…Entre los no respondedores se reporta que 21,9% son fumadores, posiblemente por la disminución de las respuestas inmunes (21) . Se sabe que el tabaquismo reduce la respuesta antigénica de los linfocitos T helper 1 (19) . El acceso a la vacuna HB en personal de salud no es universal (9) .…”
Section: Discussionunclassified
“…All HCWs, who are recently vaccinated should undergo anti-HBs testing, performed 1-2 months after administration of the last dose of the vaccine. Age, gender, obesity, smoking, immunity, and genetic factors may be responsible for reduced immune response to vaccination as documented in various Indian research studies [17,18]. An anti-HBs titer less than 10mIU/ml is regarded as nonresponsive, levels between 10 and 100 mIU/ml are considered as hypo response and more than 100mIU/ml is considered as high level of immunity following vaccination.…”
Section: Original Research Articlementioning
confidence: 99%
“…Poor seroprotection rates to hepatitis B vaccine are documented in subjects of older age group, Body Mass Index (BMI) ≥ 25, smokers and poor nutritional status [17,18].This makes it necessary to identify the individuals who are hypo responsive to vaccination thus taking necessary actions. The need for the present study is becoming increasingly important in Indian scenario to create awareness and ensure complete protection from Hepatitis B infection in high risk individuals particularly among health care workers.…”
Section: Original Research Articlementioning
confidence: 99%